Analysis of the Rayleigh wave field due to a tangential load applied on the surface of a coated elastic half-space - Şahin, Onur (Communications Series A1 Mathematics & Statistics, 2020)
The paper deals with 3D dynamic response of a coated elastic half space subject to in-plane surface loading. The problem is formulated by a pair of elliptic equations over the interior and a two dimensional singularly perturbed hyperbolic equation expressed in terms of shear wave potentials along the interface. As an example, a point force acting one of the in-plane axis is considered and the integral solution of the normal displacement along the interface is derived through the use of the relation between the wave potentials.